TINJAUAN YURIDIS TERHADAP PENERAPAN DEPONERING DIKAITKAN DENGAN ASAS EQUALITY BEFORE THE LAW DAN ASAS LEGALITAS - Khairunnisa Khairunnisa; Mexsasai Indra; Ferawati Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Waiver of criminal cases for the sake of public interest or can be referred to as “deponering” is the embodiment of the opportunistic principle that has been legitimized by the state through Article 35 letter c of Law No. 16 of 2004 concerning the Republic of Indonesia Attorney General's Office and Article 14 letter h of the Law Code. Criminal Procedure. In fact, what should be an important note for the government and law enforcement officials is that from the perspective of the general public who do not understand the law comprehensively.This type of research is normative juridical research. In this research, the researcher discusses the principles of law, namely the principle of equality before the law, namely equality before the law. Then also using the legality principle which is the principle that determines that no action is prohibited and punishable if it is determined in advance in legislation, known in Latin as Nullum Delictum Nulla Poena Sine Praevia Lege Poenali (no offense, no punishment without advance regulation).The conclusions that can be obtained from the research results are: First, there is no derivative regulation in interpreting the meaning of the "public interest" so that it becomes a multi-interpretation area and contradicts the legality principle where the legality principle requires rules first, because the regulation does not can be applied if legality is not written about the derivative rules. This means that there are misinterpretations and legal findings that occur in interpreting waivers in the public interest so that it is not relevant to our ideals as a rule of law. Second, the criteria for the Attorney General to link legal interests and public interests in granting deponering basically do not have standard rules and contradict the principle of legality which requires prior rules in order to achieve legal certainty. If it is in the public interest basically the Attorney General, before making a waiver of the case in the public interest, he first discusses it with the state power bodies that are related to the case, either directly or indirectly.Keywords: Deponering, General Attorney, Equality Before The Law, Attorney